Variation and Diagnostic Power of the Internal Transcribed Spacer 2 in Mediterranean and Atlantic Eolid Nudibranchs (Mollusca, Gastropoda) - Garzia, Matteo; Mariottini, Paolo; Salvi, Daniele; Furfaro, Giulia (Frontiers in Marine Science, 2021)
Mediterranean marine biodiversity is still underestimated especially for groups such as nudibranchs. The identification of nudibranchs taxa is challenging because few morphological characters are available and among them chromatic patterns often do not align with species delimitation. Molecular assessments helped unveiling cryptic diversity within nudibranchs and have been mostly based on mitochondrial markers. Fast evolving nuclear markers are much needed to complement phylogenetic and systematic assessments at the species and genus levels. Here, we assess the utility of the nuclear Internal Transcribed Spacer 2 (ITS2) to delimit species in the eolid nudibranchs using both primary and secondary structures. Comparisons between the variation observed at the ITS2 and at the two commonly used mitochondrial markers (COI and 16S) on 14 eolid taxa from 10 genera demonstrate the ability of ITS2 to detect congeneric, closely related, species. While ITS2 has been fruitfully used in several other mollusc taxa, this study represents the first application of this nuclear marker in nudibranchs.